Systematic literature review on Internet-of-Vehicles communication security. (December 2018) - Abu Talib, Manar; Abbas, Sohail; Nasir, Qassim; Mowakeh, Mohamad Fouzi
Currently, the popularity of Internet-of-Vehicles technology and self-driving cars are increasing rapidly. Several companies are investing in this field and are competing to release the latest and safest autonomous cars. However, this rapid Internet-of-Vehicles development also creates many security problems, which are considered a significant threat both to industry and to consumers. As a result, there is an urgent need to study the possible security threats and different solutions that can ensure the safety of drivers and also the security of industry. This research article focuses on examining the systematic literature on Internet-of-Vehicles and security. It also provides comprehensive and unbiased information regarding various state-of-the-art security problems, solutions, and proposals in vehicular ad hoc networks and Internet-of-Vehicles. Systematic literature review is used for more than 127 different research articles published between the years 2010 and 2018. The results of the systematic literature review used are categorized into the following three main categories: (1) the different types of attacks on Internet-of-Vehicles, (2) the different solutions that can be implemented to solve the threats, and (3) the performance outcomes.